Logistic regression analysis to determine the gender of bulbul (family: pycnonotidae) using external morphological characters - Siti Fairuz, Othman (Universiti Malaysia Sarawak, (UNIMAS), 2007)
Bulbul (Family: Pycnonotidae) are monomorphic birds. The morphometric study was conducted by using Sarawak Museum dry specimen of bulbuls. Seven selected external morphological characters were measured to differentiate between males and females by using logistic regression. Significant difference were observed in wing length (WL) of yellow-vented bulbul (Pycnonotus goivier goudini), tarsus (TR) of black-and white bulbul (P. melanoleucos), bill length (BL) of straw-headed bulbul (P. zeylanicus), bill depth (BD) and wing length (WL) ofolive-winged bulbul (P. plumosus) and bill depth (BD), bill width (BW) and tarsus (TR) of puff-backed bulbul (P. eutilotus). Black-headed bulbul (P. atriceps) and grey-bellied bulbul (P. cyaniventris) show no differences between males and females based on external morphological features. Percentage of successful prediction for yellow-vented bulbul was 66.67%, 62.07% for black-and-white bulbul, 83.33% for straw-headed bulbul, 61.11% for olive-winged bulbul and 67.86% for puff-backed bulbul.